Cerebrospinal Fluid Aβ42 Levels: When Physiological Become Pathological State. (11th November 2015) - Martorana, Alessandro; Di Lorenzo, Francesco; Belli, Lorena; Sancesario, Giuseppe; Toniolo, Sofia; Sallustio, Fabrizio; Sancesario, Giulia Maria; Koch, Giacomo
Summary: Impaired amyloid beta (A β ) metabolism is currently considered central to understand the pathophysiology of Alzheimer's disease (AD). Measurements of cerebrospinal fluid A β levels remain the most useful marker for diagnostic purposes and to individuate people at risk for AD. Despite recent advances criticized the direct role in neurodegeneration of cortical neurons, A β is considered responsible for synaptopathy and impairment of neurotransmission and therefore remains the major trigger of AD and future pharmacological treatment remain A β oriented. However, experimental and clinical findings showed that A β peptides could have a wider range of action responsible for cell dysfunction and for appearance of clinico‐pathological entities different from AD. Such findings may induce misunderstanding of the real role played by A β in AD and therefore strengthen criticism on its centrality and need for CSF measurements. Aim of this review is to discuss the role of CSF A β levels in light of experimental, clinical pathologic, and electrophysiological results in AD and other pathological entities to put in a correct frame the value of A β changes.